Practical Transfusion Medicine - Murphy, M; Pamphilon, D; Heddle, N (John Wiley and Sons, 2013)
Practical Transfusion Medicine Fourth Edition Edited by Michael F. Murphy, Professor of Blood Transfusion Medicine, University of Oxford; Consultant Haematologist, NHS Blood and Transplant and Oxford University Hospitals, Oxford, UK. Derwood H. Pamphilon, formerly Consultant Haematologist, NHS Blood and Transplant; Honorary Clinical Reader, Department of Cellular and Molecular Medicine, University of Bristol, Bristol, UK. Nancy M. Heddle, Director, MTRP, Professor, Department of Medicine, McMaster University, Hamilton, Ontario, Canada. The pace of change in transfusion medicine is relentless, with new scientific and technological developments. In addition, efforts are continuing to improve clinical transfusion practice and avoid the use of blood wherever possible. This fourth edition continues to be a concise and comprehensive guide to transfusion medicine. It has been thoroughly revised and updated throughout. The scope of the book has been broadened by including more international authors and a new co-editor, Professor Nancy Heddle, an expert in evidence-based transfusion medicine. Practical Transfusion Medicine is divided into seven main parts, each of which guide the reader systematically through the key areas of the speciality: - Principles of transfusion medicine - Complications of transfusion - Practice in blood centres and hospitals - Clinical transfusion practice - Alternatives to transfusion - Cellular and tissue therapy and organ transplantation - Development of the evidence base for transfusion. This book is ideal for trainee/resident haematologists revising for examinations and as a reference source for clinical and scientific staff working in the field of transfusion medicine. This edition first published 2013. © 2001, 2005, 2009, 2013 John Wiley and Sons Ltd.